The Wiley Blackwell handbook of the psychology of training, development, and performance improvement - Kraiger, Kurt, 1957- (John Wiley & Sons, 2015)
The latest Wiley Blackwell Handbook of Organizational Psychology uses a psychological perspective, and a uniquely global focus, to review the latest literature and research in the interconnected fields of training, development, and performance appraisal. Maintains a truly global focus on the field with top international contributors exploring research and practice from around the worldOffers researchers and professionals essential information for building a talented organization, a critical and challenging task for organizational success in the 21st centuryCovers a diverse range of topics, in.